Rancang Bangun Sistem Informasi Perizinan Santri Berbasis Web di Pesantren Muhammadiyah Al-Furqon - Faisal Egi Putra Sumpena; Alfadl Habibie; Taofik Muhammad (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2026)
Advances in information technology have had a positive impact on various fields, including administrative management in the educational sector. At the Muhammadiyah Al-Furqon Islamic Boarding School in Tasikmalaya—the subject of this study—the process of issuing student leave permits was previously conducted manually, often leading to challenges such as delays in record-keeping, data errors, and inefficiency. Additionally, parents had to visit the boarding school in person to request a permit, which did not always guarantee approval. As a solution, this study designed and developed a web-based student leave permit information system that can assist administrators in automatically recording and printing permission letters, as well as make it easier for parents to submit permission requests online. This study employed the Research and Development (R&D) method using the Waterfall development model. Data collection was conducted through observations, interviews, literature reviews, and questionnaires. The feasibility study results, using the TELOS method, were as follows: Technical (96.7%), Economic (100%), Legal (100%), Operational (90.1%), and Schedule (88.5%), resulting in an overall score of 95.1%. These results fall into the